STUDY OF COMMUNITY SATISFACTION WITH CORPORATE SOCIAL RESPONSIBILITY (CSR) PROGRAMS PT. SOCFINDO KEBUN SEUNAGAN NAGAN RAYA DISTRICT - Rika Yanti; Aswin Nasution (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Corporate Social Responsibilityor CSR is one of the most popular efforts to gain public trust in the company. This is a form of social equilibrium between the company and the surrounding community, so information on the satisfaction of the community around the company regarding the CR carried out needs to be known for further improvement of CSR programs. This research was conducted to determine the level of community satisfaction with the CSR program carried out by the oil palm plantation company PT. Socfindo plantation Seunagan – Aceh. The results of the study show that the CSR program has not provided satisfaction for the communities around the plantations. Attributes of the process of capturing citizens' aspirations at the beginning of the program had the highest level of satisfaction, while attributes of capital assistance provided by companies to entrepreneurs gave the lowest satisfaction. In connection with CSR as a corporate concern program for the surrounding community, PT. Socfindo Seunagan Plantation needs to involve the local community as a stakeholder in the planning and implementation of CSR, while still taking into account the priority needs of the surrounding community.